The Formulation, Evaluation and Physical Stability Test of Aloe Vera (Aloe vera L.) Extract Gel Preparations with the Addition of Sodium Metabisulfite: Formulasi, Evaluasi dan Uji Stabilitas Fisik Sediaan Gel Ekstrak Lidah Buaya (Aloe vera L.) dengan Penambahan Sodium Meta - Wiji Purnamasari, Yulia; Juniarti; Rahmah, Nunung Ainur (Medicra (Journal of Medical Laboratory Science/Technology), 2024)
Aloe vera (Aloe vera L.) is a plant that has many benefits, such as anti-inflammatory, anti-fungal, antibacterial, and moisturizing the skin. Gel preparations are easily contaminated by bacteria and fungi, so it is necessary to consider adding sodium metabisulfite as a preservative. The aim of this research is to prove the effectiveness of using sodium metabisulfite as a preservative for aloe vera extract gel preparations. The aloe vera plant (Aloe vera L.) was extracted using the maceration method for 3x24 hours using methanol solvent. This research used 5% aloe vera (Aloe vera L.) extract, and in the evaluation and stability test used 4 variation formulations using a carbomer base, only gel base (F1), gel base with the addition of sodium metabisulfite (F2), gel base with 5% aloe vera extract (F3), and gel base with 5% aloe vera extract and sodium metabisulfite (F4). The evaluations carried out were organoleptic tests, pH tests, viscosity tests, and ALT (Total Plate Number) tests and AKK (Yeast Mold Number) tests. The physical stability test is carried out for 3-14 days. The extract yield test results obtained were 4.892%. Organoleptic tests on F1, F2, F3 and F4 did not show changes in color, odor and texture, whereas on day 14 changes in color, odor and texture began to occur in the F3 preparation. The pH test showed pH results of 4.67 (F1), 4.9 (F2), 5 (F3) and 5.1 (F4). The viscosity test shows the gel has a viscosity of 2760 cps (F1), 2650 cps (F2), 2590 cps (F3), and 2575 cps (F4). The ALT and AKK tests showed that there was an increase in the value of the F3 preparation. So based on these results it can be concluded that the best gel preparation is F4